Implementasi Bahasa Arab terhadap Perkembangan Ekonomi Masyarakat di Era Modern - Misbahus Surur (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2020)
As long as we stick to the Qur'an and Hadith in every activity of our lives, during that time, Arabic has a role in it. This is no exception in the economic field, especially those based on Islamic law. Although lately there have been various translations into several languages, even to all languages ??on earth, it cannot be denied that it requires a comprehensive understanding of Arabic before carrying out the translation process, especially the languages ??of the two sources of Islamic law use diction. and/or editorial which cannot be easily transliterated or interpreted. Thus, as long as there are Muslims in this world, so long as the existence of the Arabic language will continue and its impact on every activity of life is still strong, including in terms of the economic development of society.